Avaliação do efeito de extratos de batata e alecrim sobre as colinesterases em um modelo de diabetes tipo 1 em ratos - Dutra, Eduardo José Machado (2014)
Type 1 diabetes (T1D) is a disease characterized by the individual's inability to produce the hormone insulin due to destruction of pancreatic β-cells by the immune cells of the organism itself. So far, there is no 100% effective therapy for treating the symptoms of T1D. Current treatments involve constant monitoring of blood glucose levels and regular insulin injections. Inflammatory processes are associated with the development and progression of T1D, and so new therapies involving drugs with anti-inflammatory properties have been the subject of increasing interest in the scientific community. Polyphenols are a class of heterocyclic compounds that include anthocyanins and rosmarinic acid, both known for their antioxidant and anti-inflammatory properties. We studied the effects of two polyphenol rich extracts (cooked potato and rosemary) and a concentrate of anthocyanins in a model of type 1 streptozotocin-induced diabetic rats. The extracts were administered by gavage for 30 days. After this period, the rats were euthanized and we assessed acetylcholinesterase (AChE) activity in lymphocytes and serum butyrylcholinesterase (BuChE) activity, because of the importance of these enzymes as biomarkers of inflammation. The activities of both enzymes were shown to be increased in diabetic rats compared to controls. The cooked potato peel extract and concentrated anthocyanins did not altered AChE activity in lymphocytes, probably due to low bioavailability, while rosemary extract was a potent inhibitor and reverted the activity to normal levels. None of the treatments had any effect on serum BuChE activity. These results support the involvement of inflammatory processes on TD1 pathology and present the rosemary extracts as a promising alternative for future phytochemical therapies for the treatment of inflammatory-related diseases, such as type 1 diabetes.